2007
DOI: 10.1634/theoncologist.12-4-438
|View full text |Cite
|
Sign up to set email alerts
|

Disease Progression Following Imatinib Failure in Gastrointestinal Stromal Tumors: Role of Surgical Therapy

Abstract: Gastrointestinal stromal tumors (GISTs) represent the most common mesenchymal neoplasms of the GI tract. The optimal management of GISTs has been evolving rapidly over the past 5 years and depends on proper histopathologic and radiologic diagnosis as well as appropriate multidisciplinary medical and surgical treatments. Complete surgical resection of primary localized GIST with negative margins remains the best therapeutic option today. In the setting of locally advanced or metastatic disease, imatinib mesylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…The significance of endoscopic ultra-sound guided fine needle aspiration has been pointed out in several studies 13 and the reported accuracy is 80.0 o %-85.0 o %. However the present case report section from core biopy has shown fibrofatty tissue containing a few chronic inflammatory cells with no gastrointestinal stromal tumor or malignancy which is inconsistent with other findings 11,12 .…”
Section: Figure Iv: Showing the Resected Mass With Part Of Sigmoid Coloncontrasting
confidence: 99%
See 1 more Smart Citation
“…The significance of endoscopic ultra-sound guided fine needle aspiration has been pointed out in several studies 13 and the reported accuracy is 80.0 o %-85.0 o %. However the present case report section from core biopy has shown fibrofatty tissue containing a few chronic inflammatory cells with no gastrointestinal stromal tumor or malignancy which is inconsistent with other findings 11,12 .…”
Section: Figure Iv: Showing the Resected Mass With Part Of Sigmoid Coloncontrasting
confidence: 99%
“…This is consistent with the present case report. The preoperative percutaneous biopsy should not be used because it is associated with a significant risk of tumor rupture or dissemination 12 . The significance of endoscopic ultra-sound guided fine needle aspiration has been pointed out in several studies 13 and the reported accuracy is 80.0 o %-85.0 o %.…”
Section: Figure Iv: Showing the Resected Mass With Part Of Sigmoid Colonmentioning
confidence: 99%
“…Although, the diagnostic procedure includes several examinations, like barium examination of the GI tract, computer tomography and angiography, none of them can establish the diagnosis. The preoperative percutaneous biopsy should not be used because it is associated with a significant risk of tumor rupture or dissemination [ 20 ]. The significance of endoscopic ultra-sound guided fine needle aspiration has been pointed out in several studies and the reported accuracy is 80% - 85% [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of surgery for patients aVected by GIST has changed due to the neo-adjuvant use of imatinib Andtbacka et al 2007;Gronchi et al 2007;Raut et al 2006;DeMatteo et al 2007;Scaife et al 2003;Wu et al 2003;Rutkowski et al 2006;Haller et al 2007;Jamali et al 2007). Imatinib may reduce the tumor size and increase the rate of complete resection of a large tumor mass, which was unresectable before systemic therapy (Andtbacka et al 2007).…”
Section: Discussionmentioning
confidence: 99%